KRISIS NILAI-NILAI SOSIAL DALAM KELUARGA - Emi Handrina (Ensiklopedia of Journal, 2020)
A harmonious family and a family that can overcome a problem in harmony and wisely, so that it can improve the quality of childrens growth ang development towards a better direction. This is very influenced by the role of parent and the environment.